Tinjauan Hukum Islam dan Hukum Positif Tentang Praktik HIT and RUN dalam Jual Beli Online di Sosial Media Pada Toko Madina Moslem Wear di Ponorogo - Restiani Restiani; Suad Fikriawan; Diyan Putri Ayu (Social Science Academic, 2023)
Hit and run can also be interpreted as consumers who have questions about goods or have ordered goods nd promised to pay at a predetermined time,but at maturity they still do not pay and eventually disappear without confirmation, some block sellers from being billed for payment. In general, this can cause losses that vary depending on the type of business sector and the product or service offered and the system used. So, entrepreneurs must prepare tactics to overcome, or prevent such customers. The motives underlying hit and run actions by customers cannot be ascertained clearly. However, business actors can only provide analysis or evaluate things that happened and the reasons a person took such actions. Ordering goods online with a pre order system at the Madina Moslem Wear store is done using the Instagram and Whatsapp applications by filing in the format specified by seller, such as filling in the name of the customers who ordered, ordered goods, whatsapp number and instagram account name. Then the seller gives the option to the customers to place an order for goods and a make a payment in advance or may also make a payment when the goods are available but with conditions not hit and run.